1999
DOI: 10.1007/s002340050757
|View full text |Cite
|
Sign up to set email alerts
|

Post-procedure migration of Guglielmi detachable coils and Mechanical detachable spirals

Abstract: We describe a previously unreported complication of the use of Guglielmi detachable coils and Mechanical detachable spirals in endovascular treatment of intracranial aneurysms. We document four cases in which migration of part of a coil into the parent artery occurred after completion of the procedure. Possible mechanisms are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 3 publications
1
37
1
Order By: Relevance
“…[9][10][11] Detached coil herniation into the parent artery usually occurs at the end stage of the procedure. It may result from instability of the coil in the aneurysm sac, excessive embolization, microcatheter removal, or the coil being pushed out by subsequent coil embolization.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Detached coil herniation into the parent artery usually occurs at the end stage of the procedure. It may result from instability of the coil in the aneurysm sac, excessive embolization, microcatheter removal, or the coil being pushed out by subsequent coil embolization.…”
Section: Discussionmentioning
confidence: 99%
“…Yamao et al reported that in a Japanese cohort of cases involving coil protrusion into the parent artery, APT was halted within 6 months in 76.5% of cases [17]. On the other hand, delayed restenosis after coil protrusion has been reported [18,19]. In these cases, thrombus formation is presumed to be the cause of restenosis; therefore, long-term APT should be continued if a long length of coil protrudes into the parent artery.…”
Section: Apt and Delayed Ischemic Events After Coil Protrusion Into Pmentioning
confidence: 99%
“…Coil herniation or fracture during wide-necked aneurysm embolization are more often reported in aneurismal endovascular procedures performed without stent-assistance [14][15][16] . Cases in which migration of part of a coil into the parent artery occurred after the procedure have also been described 17 . This post-procedural migration of coils could be either associated with wide neck aneurysms that are packed with undersized coils or have been tightly packed in the neck region with coils independent from the main coil basket 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Cases in which migration of part of a coil into the parent artery occurred after the procedure have also been described 17 . This post-procedural migration of coils could be either associated with wide neck aneurysms that are packed with undersized coils or have been tightly packed in the neck region with coils independent from the main coil basket 17 . Different strategies have been reported in case of peri-procedural complications such as prolapsed, unraveling or fractured coils.…”
Section: Discussionmentioning
confidence: 99%